Further records of predatory phytoseiid mites (Phytoseiidae, Acari) from the Philippines - Corpuz-Raros, Leonila A. (2001)
Further records of Philippine predatory mites belonging to the family Phytoseiidae are presented including descriptions of four new species (Amblyseius davaoensis Corpuz-Raros, A. syzygii Corpuz-Raros, A. zamboangaensis Corpuz-Raros, and Paraphytoseius binuang Corpuz-Raros), and records of three new species (A. markwelli Schicha, A. victoriensis Womersley, and A. womersleyi Schicha). The newly discovered males of four previously known species (A. darwinensis Schicha, A. semirregularis Schicha and Corpuz-Raros, Proprioseius schichai Corpuz-Raros and Typhlodromus diumbokus Schicha and Corpuz-Raros) are described for the first time. New plant habitats for 56 species as well as new distribution records of 18 species of phytoseiids in various Philippine islands are also reported.
Keywords: Mites; Taxonomy